Effectiveness of the First German-Language Group Psychotherapy Manual to Accompany Short-Term Treatment in Methamphetamine Dependence - Petzold, Johannes; Weber, Benjamin; Bassett, Tyler Ray; Bauer, Michael; Bernhardt, Nadine; Groß, Cornelius; Hasler, Helena; Schützwohl, Matthias; Pilhatsch, Maximilian (Frontiers in Psychiatry, 2020)
Background: Methamphetamine abuse is expanding in Europe, leading to a shortfall in medical care for related disorders in many regions. Research focusing on the effectiveness and feasibility of methamphetamine-specific treatment programs is scarce, especially in short-term settings. Methods: To this end, we treated 31 patients with methamphetamine dependence using a new group psychotherapy manual added to standard psychiatric care. Trained research assistants recorded demographic, illness and treatment variables using a standardized interview at baseline and a follow-up visit 3 months later. Outcome and process variables for this intervention encompassing 15 modules for qualified detoxification and motivation of patients with methamphetamine dependence are reported. Results: Retention and abstinence rates as well as acceptance and feasibility in daily routine were assessed positively. Patients with an unsuccessful outcome were characterized by longer regular methamphetamine use (t = −2.513, df = 29, p = 0.018) and a shorter abstinence period at baseline (U = 74.500, z = −1.808, p = 0.072). Among the demographic and clinical variables, the only predictor significantly increasing the odds of a successful outcome was a shorter period of regular methamphetamine use (OR = 1.318, CI 95% for OR = 1.021–1.700, b = 0.276, SE = 0.130, p = 0.034). Conclusions: This freely available therapy manual can help counter the shortfall in available psychotherapeutic interventions for patients with methamphetamine dependence in German-speaking countries. The routinely assessed parameters duration of regular methamphetamine use and abstinence before treatment were associated with outcome and may be used to personalize therapeutic strategies.